Changes in Tax Legislation and Social Responsibility of Taxpayers and Legislative Institutions - Štager, Vesna (Naše gospodarstvo/Our economy, 2018)
The article deals with the cost of tax compliance which arises for taxpayers from tax complexity and the constant changes in tax legislation. A socially responsible institution for the fiscal aggression is the Financial Administration of the Republic of Slovenia, as its powers and responsibilities creates the tax position of individuals, businesses and the entire economy. The aim of our research is to encourage socially responsible behaviour of legislation institutions in adopting the tax legislation, which will help to improve the social responsibility of taxpayers and increase tax compliance.